Green supply chain management: impact on environmental performance and firm competitiveness. (8th April 2019) - Tan, Cheng Ling; Zailani, Suhaiza Hanim Mohd.; Tan, Sieow Chin; Yeo, Sook Fern
Unrestrained industrialisation resulting in environmental pollution has mobilised the unstinting endeavours of scientist, researchers, policy makers and ecologist in a quest to rapidly unearth solutions to mitigate further environmental deterioration. One promising ongoing development is green supply chain management (GSCM), which promises a reduction of pollution and waste in manufacturing. GSCM achieves this through the mechanism of improving manufacturing efficiency, by reducing costs, enhancing product quality and improving product delivery. This study applies the natural resource-based view, and quantitatively examines the impact of the implementation of GSCM on firm environmental performance, and firm competitiveness. Data was collected from 122 sampled firms, analysed, and evaluated in two ways. Firstly, using partial least squared-structured equation modelling (PLS-SEM), results indicate that 'green procurement', and 'green supplier and customer collaboration', have a significant positive relationship with both firm environmental performance, and, firm competitiveness. Secondly, using importance-performance matrix analysis (IPMA), both 'green procurement' and 'green supplier and customer collaboration' are mapped in the high in importance/high-performance quadrant. The practical recommendations are for organisations to prioritise efforts and resources towards 'green procurement' and 'green supplier and customer collaboration' in order to maximise the return on 'green' investment.